Benthic diatom communities from two salt marshes of the St. Lawrence Estuary (Canada) - De Sève, Michèle; Poulin, Patrick; Pelletier, Émilien; Lemarchand, Karine (Revue des sciences de l'eau / Journal of Water Science)

(untitled) (Université du Québec - INRS-Eau, Terre et Environnement (INRS-ETE), 2010)
Microphytobenthic diatom communities were investigated in the high and low sections of two salt marshes of the Lower St. Lawrence Estuary (eastern Canada): one featuring a sandy low marsh zone (Pointe-aux-Épinettes; PE) and one with a muddy low marsh area (Pointe-au-Père; PP). Based on diatom composition and diversity, bacterial abundance, chlorophyll-a, phaeopigments and geochemical analyses (Corg, Ntot, granulometry, extracellular polymeric substances), the PP high marsh area appeared to be singular compared to the other sampling sites. Estimated surface biomass ranged from 11 to 71 g C•m-2 in the PE marsh and from 24 to 486 g C•m-2 in the PP marsh. A higher diversity of diatom species was observed in the PP high marsh area with a dominance of epipelic forms, in opposition to the dominant epipsammic forms at the other sites. Statistical analyses showed that diatom density was mainly affected by nutrient availability while the relative abundance of epipelic and epipsammic species was related to sediment grain size. This study provides original data on the composition of benthic diatoms in surface sediments in St. Lawrence saltmarshes during summer time that represent the first step to the determination of the DBI (Diatom biological index) of these northern environments.